Implementing clinical guidelines to promote integration of mental health services in primary health care: a qualitative study of a systems policy intervention in Uganda - Wakida, Edith K.; Obua, Celestino; Musisi, Seggane; Rukundo, Godfrey Z.; Ssebutinde, Peter; Talib, Zohray M.; Akena, Dickens; Okello, Elialilia S. (International Journal of Mental Health Systems, 2019)
Background: Clinical practice guidelines (CPG) are developed based on a synthesis of evidence regarding the best options for the assessment, diagnosis and treatment of diseases and are recognized as essential quality improvement tools. However, despite growing availability of CPG, research evaluating their use for mental disorders in Uganda is lacking. For a successful implementation of CPG to be achieved, a number of considerations need to be put in place. Objective: This study aimed to assess the feasibility and acceptability of the educational intervention that we developed towards improvement of the primary health care providers (PHCPs) uptake of the Uganda Clinical Guidelines (UCG) in integrating mental health services into PHC in Mbarara district, southwestern Uganda. Methods: This was a descriptive cross-sectional qualitative study with a semi-structured in-depth interview guide. The educational intervention we were assessing had four components: (i) summarized UCG on common mental disorders; (ii) modified Health Management Information System (HMIS) registers to include mental health; (iii) clinician’s checklist outlining the steps to be followed; and iv) support supervision/training. Results: Six themes emerged from the study while the components of the intervention formed the apriori subthemes. Key results based on the subthemes show: (i) summarized UCG: the participants liked the packaging stating that it eased their work, was time saving and user friendly; (ii) modified register: participants appreciated the modifications made to the register updating the existing record in the Health Management Information System (HMIS) registers to include mental health disorders; (iii) TRAINING and support supervision: the PHCPs attributed the success in using the summarized UCG to the training they received, and they further expressed the need to regularize the training in assessment for mental health and support by the mental health specialists. Conclusion: Our study demonstrates that the use of summarized UCG, modified HMIS registers to include mental health, training and support supervision by mental health specialists in implementing the UCG in integrating mental health at PHC settings is feasible and acceptable by the PHCPs in Mbarara district, southwestern Uganda. Given the need for improved mental health care in Uganda, this intervention could be rigorously evaluated for effectiveness, scalability and generalizability
Keywords: Uganda Clinical Guidelines; Uptake; Integration of mental health services; Primary health care providers